Did India's demonetization policy curb stone-pelting in Indian-administered Kashmir. (17th November 2021) - Fair, C. Christine; Ghotane, Digvijay; Patel, Parina
ABSTRACT: On 9 November 2016, India's Prime Minister Narendra Modi announced his 'demonetization' policy which rendered all Rs. 500 and Rs. 1000 notes null and void. His government claimed that this policy, among other things, would curb stone-pelting in India's restive Jammu and Kashmir by rendering valueless the copious illegal currency that, according to India, Pakistan pumped into the state to pay protestors to throw stones. Subsequently, New Delhi claimed success despite countervailing evidence for this claim. Here, we assemble a novel dataset to evaluate these assertions. After controlling for other factors that may explain variation in stone-pelting, we find that demonetization corresponded to increased stone-pelting. This finding is important for at least two reasons. First, Indian efforts to depict all protests in Jammu and Kashmir as the result of Pakistani payments both delegitimize Kashmiris' grievances by reducing them to anti-state behaviors and diminish public appetite for addressing those grievances. Second, the current populist Indian government, which caters to Hindu nationalists, selectively curates facts to justify its actions, big and small, to the detriment of democratic accountability and governance.